THE FORMS AND MEANINGS OF ANTHROPOMORPHIC METAPHORS IN PAE LANGUAGE - Bustan, Fransikus; Semiun, Thresia Trivict; Ulinsa, Ulinsa (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2022)
This study describes the forms and meanings of anthropomorphic metaphors in Pae dialect in view of cultural linguistics. This study is descriptive. The methods of data collection were observation, interview, and documentary study. The techniques of data collection were recording, elicitation, and note-taking. The sources of data were the native speakers of Pae language represented by two key informants. Data were analyszed qualitatively by using inductive method. The results of study show that the forms and meanings of anthropomorphic metaphor in Pae language have unique and specific characteristics, as can be seen in such terms as ulung wae, mata wae, kinga kue, wewa kue, nggolo kue, lime kerosi, tuka nepe, tedu nepe, wa’i woko, and tedu woko. The results of study might be beneficial to support the study of language as the mirror of culture shared by a people as members of an ethnic group with special reference to Pae language as the mirror of Pae culture serving both as the sense of identity and as the symbol of identity for Pae people as members of Pae ethnic group.